Strain energy contributions on the bainitic phase transformation in a CrMoV steel during continuous cooling. (5th October 2018) - Reisinger, S.; Kozeschnik, E.; Ressel, G.; Keckes, J.; Stark, A.; Marsoner, S.; Ebner, R.
Abstract: The bainitic phase transformation during continuous cooling in low alloyed steels is a complex process since many different reactions are taking place simultaneously. Since all of them are rather sensitive to the applied cooling rates, the present study investigates the mechanisms taking place during the bainitic phase transformation by using a comprehensive set of methods including in-situ high energy X-ray diffraction combined with dilatometry, ex-situ microstructure characterization by means of scanning and transmission electron microscopy including electron back scatter diffraction. The results demonstrate that the phase transformation characteristics changes from a continuous to a two-stage behaviour with decreasing cooling rate. The reason for this change is discussed and explained on basis of an adapted T0 ′-limit concept taking an additionally required strain energy between about 950 and 1100 J/mol in the energy balance into account. Apart from the observed transformation characteristics, it is also shown that the amount of blocky instead of film like retained austenite increases with decreasing cooling rate. Graphical abstract: Unlabelled Image Highlights: The transformation characteristics from austenite to bainite during continuous cooling changes with decreasing cooling rate High amounts of retained austenite are present in the final microstructure in two distinct morphologies: films and blocks This high amounts of retained austenite cannot be explained by a T0 '-line with a strain energy contribution of 400 J/mol Simulations and calculations of the strain energy depending on the bainitic microstructure yield values of 950 to 1100J/mol